The Effect of CSR and GCG Disclosure on Firm Value and Moderated by Operating Margin - Juman Sahbandi; Sriyono Sriyono; Sri Suryaningsum (Pusat Riset dan Inovasi Nasional, 2025)
This research investigates the influence of Corporate Social Responsibility (CSR) disclosure and Good Corporate Governance (GCG) practices on firm value, with operating margin serving as a moderating variable. The study focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023, a sector characterized by high environmental and social impact as well as substantial capital intensity. CSR disclosure is measured using sustainability-based disclosure indices that reflect companies’ commitment to social, environmental, and economic responsibilities. Meanwhile, GCG is evaluated through governance indicators that represent transparency, accountability, responsibility, independence, and fairness. Firm value is proxied using market-based measurements, particularly the Price-to-Book Value (PBV), while operating margin is incorporated to capture operational efficiency and profitability. The empirical results demonstrate that CSR disclosure and GCG practices have a significant positive effect on firm value, indicating that stakeholders respond favorably to companies that implement sustainable practices and strong governance structures. Furthermore, operating margin is found to strengthen the relationship between CSR, GCG, and firm value, suggesting that firms with higher operational profitability are better able to translate sustainability initiatives and governance quality into enhanced market valuation. These findings underscore the importance of integrating sustainability disclosure, effective corporate governance, and operational efficiency as strategic instruments to improve firm value in the mining industry.